MicroRNAs regulate tolerance mechanisms in sugarcane (Saccharum spp.) under aluminum stress - Leite Silva, Joice de Oliveira; Silva, Renan Goncalves da [UNESP]; Nogueira, Lucas de Faria; Zingaretti, Sonia Marli (Brazilian Soc Plant Breeding, 2021)
The agricultural yield of sugarcane (Saccharum spp.) is influenced by various abiotic stresses, including aluminum toxicity (Al3+). MicroRNAs (miRNAs) play a role in plant tolerance to such stresses by modulating the expression of several important target genes involved in plant growth. This study investigated the possible tolerance mechanisms of two sugarcane genotypes (CTC-2 and R8855453) under Al3+ stress through miRNA expression profiles and in silico analysis of target genes. The expression data obtained using RT-qPCR and coexpression network analysis identified two possible regulatory mechanisms in the tolerant genotype (CTC-2) under Al3+ stress. miR395 was involved in Al3+ detoxification, whereas miR160, miR6225-5p, and miR167 participated in the process of lateral root formation, conferring tolerance to the genotype. These findings might be useful for biotechnological strategies that aim for miRNA silencing or gene overexpression and provide subsidies for future genetic improvement programs aimed at the development of abiotic stress-tolerant sugarcane genotypes.
Keywords: Aluminum toxicity; co-expression network; RT-qPCR; Saccharum; small RNAs